A new genus of Australian Agyrtodini from Tasmania (Coleoptera: Leiodidae: Camiarinae) - Ashman, Lauren G.; Seago, Ainsley E.; Leschen, Richard A.b. (Zootaxa, 2024)
Myopagyrtes tasmanicus new genus, new species, is described from Tasmania, Australia. It has reduced eyes and the hindwings are absent, unusual features among Agyrtodini. It was collected from leaf litter in forests, typically dominated by Nothofagus. It is hypothesised as related to the genus Agyrtodes Portevin and the New Zealand genus Chelagyrtodes Szymczakowski.